Scotus on Sense, Medium, and Sensible Object - Ginocchio, David (Filosoficky Casopis, 2018)
This paper aims to examine some of Scotus’s key notions on perception in his Commentary on the De anima, focusing on the notions of sense, medium, and object. I will keep two main points of interest at hand: first, Scotus’s understanding and reception of the philosophy of perception advanced by his contemporaries, in light of his own theory of the faculties, objects, and the perfection of their respective acts; second, the distinction and classification of the external senses according to their perfection.
Keywords: duns scotus; perception; sensible object; medium; intentionality; WOS; Scopus